The ischnoceran chewing lice (Phthiraptera: Ischnocera) of bulbuls (Aves: Passeriformes: Pycnonotidae), with descriptions of 18 new species - Gustafsson, Daniel R.; Najer, Tomas; Zou, Fasheng; Bush, Sarah E. (European Journal of Taxonomy, 2022)
The ischnoceran chewing lice known from bulbuls are discussed and revised, and 18 new species are described. These are: Brueelia celer sp. nov. from Pycnonotus cafer bengalensis Blyth, 1845 and Pycnonotus cafer primrosei Deignan, 1949; Brueelia colindalei sp. nov. from Hemixos castanonotus canipennis Seebohm, 1890; Brueelia doisuthepensis sp. nov. from Alophoixus ochraceus ochraceus (Moore, 1858); Brueelia galeata sp. nov. from Alophoixus pallidus henrici (Oustalet, 1896); Brueelia hermetica sp. nov. from Pycnonotus barbatus layardi Gurney, 1879; Brueelia leiae sp. nov. from Alophoixus flaveolus burmanicus (Oates, 1899); Brueelia robertrankini sp. nov. from Pycnonotus jocosus jocosus (Linnaeus, 1758) and Pycnonotus jocosus pattani Deignan, 1948; Brueelia yunnanensis sp. nov. from Ixos mcclellandii similis (Rothschild, 1921); Guimaraesiella brunneomarginata sp. nov. from Pycnonotus goiaver samarensis Rand & Rabor, 1960 and Pycnonotus goiaver personatus Hume, 1873; Guimaraesiella caligogularis sp. nov. from Pycnonotus plumosus plumosus Blyth, 1845 and Alophoixus bres tephrogenys (Jardine & Selby, 1833); Guimaraesiella cinnamomea sp. nov. from Iole propinqua propinqua (Oustalet, 1903) and Iole viridescens cinnamomeoventris Baker, 1917; Guimaraesiella ixi sp. nov. from Ixos mcclellandii peracensis (Hartert & Butler, 1898); Guimaraesiella lorica sp. nov. from Hypsipetes leucocephalus nigerrimus Gould, 1863; Guimaraesiella mayoensis sp. nov. from Hypsipetes everetti everetti (Tweeddale, 1877); Guimaraesiella phlaoalopha sp. nov. from Alophoixus pallidus henrici (Oustalet, 1896); Philopteroides holosternus sp. nov. from Pycnonotus goiavier goiavier (Scopoli, 1786); Philopteroides longiclypeatus sp. nov. from Hypsipetes everretti samarensis Rand & Rabor, 1959; Philopteroides haerixos sp. nov. from Ixos mcclellandii holtii (Swinhoe, 1861) and Alophoixus pallidus henrici (Oustalet, 1896). The following new host records are provided: Hemixos castanonotus canipennis Seebohm, 1890, for Guimaraesiella flavala (Najer & Sychra in Najer et al., 2012); Pycnonotus blanfordi conradi (Finsch in Finsch & Conrad, 1873) for Philopteroides cucphuongensis Mey, 2004. Philopterus cucphuongensis is tentatively redescribed and illustrated based on specimens from a non-type host species. The species descriptions of the following species are amended slightly, based on re-examinations of type specimens: Brueelia alophoixi Sychra in Sychra et al., 2009; Guimaraesiella cucphuongensis (Najer & Sychra in Najer et al., 2012); Guimaraesiella flavala (Najer & Sychra in Najer et al., 2012). We propose to move Philopterus hiyodori Uchida, 1949, to the genus Craspedorrhynchus Kéler, 1938. The species Sturnidoecus acutifrons (Uchida, 1949) and Penenirmus guldum (Ansari, 1955) are considered species inquirenda. An updated checklist of ischnoceran lice known from bulbuls is provided, as well as a key to all ischnoceran species known from bulbuls.